Prelinguistic Infants, but Not Chimpanzees, Communicate About Absent Entities - Liszkowski, Ulf; Schäfer, Marie; Carpenter, Malinda; Tomasello, Michael (Psychological Science, 2009)
One of the defining features of human language is displacement, the ability to make reference to absent entities. Here we show that prelinguistic, 12-month-old infants already can use a nonverbal pointing gesture to make reference to absent entities. We also show that chimpanzees-who can point for things they want humans to give them-do not point to refer to absent entities in the same way. These results demonstrate that the ability to communicate about absent but mutually known entities depends not on language, but rather on deeper social-cognitive skills that make acts of linguistic reference possible in the first place. These nonlinguistic skills for displaced reference emerged apparently only after humans' divergence from great apes some 6 million years ago.